Braille Letter Introduction Method for Blind Children - Pratama, Zarir Abiyyuda; Darmawan, Wahyu Hari; Suparmi, Suparmi (Department of Special Education, 2024)
This study aims to understand the Braille recognition method used by teachers. The method used by the author in this study is Literature Review. With the stages of identifying, reviewing, and interpreting research. Literature review articles use publications from 2020- 2024 which can be accessed via Google Scholar, then a literature review is conducted to find related research. Blind people are individuals with visual impairments that cause obstacles in their visual function. There are two groups of blind people, namely total blindness and low vision. Braille is a tactile writing and reading system that is important for the blind. To teach Braille, there are several commonly used recognition methods, namely the scramble method, the flashcard method, the left code method, the fernald method, and the SAS (structural analytic synthetic) method. Each method has advantages and can have a positive impact on learning. Good teaching skills are needed to help the blind develop their Braille reading skills. The conclusion of the presentation is that all Braille recognition methods have a significant influence and a personal approach is needed in teaching to ensure effective understanding and learning for each blind individual